2020
DOI: 10.21203/rs.3.rs-51049/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Pandemic and its Implication on Hand Hygiene Status by Alcohol-based Hand Sanitizers Among Healthcare Workers in Jimma University Medical Center, Ethiopia

Abstract: Background: Pandemic corona virus disease (COVID-19) is a global health crisis of our time. The consistent practice of hand hygiene, especially by proper use of alcohol-based hand sanitizers in health facilities and community is a cardinal step in combating it. This study was designed to assess self-reported level of knowledge, attitude and compliance to WHO recommended hand hygiene status by alcohol-based hand sanitizers among healthcare workers during a COVID-19 pandemic in Jimma University Medical Center, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
2
7
3
Order By: Relevance
“…As knowledge is the result of awareness based on obtaining appropriate information, it is supported by a study conducted elsewhere [ 7 ]. This finding is congruent with a study conducted in the Netherlands [ 21 ] which showed high information seeking behavior is associated with a good adherence to COVID-19 Preventive measures. This might be due to the fact that if the population had prior information about the utilization and advantage of the prevention measures [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…As knowledge is the result of awareness based on obtaining appropriate information, it is supported by a study conducted elsewhere [ 7 ]. This finding is congruent with a study conducted in the Netherlands [ 21 ] which showed high information seeking behavior is associated with a good adherence to COVID-19 Preventive measures. This might be due to the fact that if the population had prior information about the utilization and advantage of the prevention measures [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with studies in Northwest Ethiopia 66.1% and 70.65% [37,57], in Nigeria 64% and in Cameroon 69% [44,47], and in Syria 63.5% [39]. But it is lower than found in other studies from Ethiopia 94.7% and 74% [41,42], Nigeria 79.5% and 80.6% [45,46], Malaysia 83.1% [51], Pakistan 86.5% and 75% [40,49], and from Bangladesh 78.9% [56]. The finding is higher than in some studies from Northwest Ethiopia 52.7% [57], from Uganda 21% [33], from Bangladesh 62.3% [68] and from Iran 59.3% [54].…”
Section: Plos Onesupporting
confidence: 90%
“…In this study, 73.4% of taxi drivers always used alcohol-based hand sanitizer. It was lower than study findings from Jimma [41], where the use of alcohol-based hand sanitizer among healthcare workers was 95.8%. The lower utilization of alcohol-based hand sanitizer in our study area might be either because of no access to hand sanitizer due to high cost or less attention to the hand sanitizer.…”
Section: Plos Onecontrasting
confidence: 71%
See 2 more Smart Citations